Analysis of Polygamy Law in Indonesia: Harmony between Islamic Law and State Law - Aminah Aminah; Asyharul Muala (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2023)
Polygamy, a practice that is widely recognized and regulated in Islamic law, often raises legal and social dilemmas in the context of Indonesia's national regulations. This research uses descriptive qualitative methods to analyze the interaction between Islamic law and Law Number 1 of 1974 concerning Marriage in Indonesia, which shows the conflict between religious norms and modern legal demands that are more inclusive. The research results show a significant gap between the law and practice of polygamy, with many cases carried out without official registration, leaving wives and children vulnerable without adequate legal protection. This study emphasizes the need for policy reform and increased law enforcement to address these social and legal problems, as well as increasing harmony between religious law and positive law, with the main aim of seeking better justice and prosperity for all involved.